Leapfrog migration and habitat preferences of a small oceanic seabird, Bulwer's petrel (Bulweria bulwerii) - Ramos, Raül (2018)
AIM: Our current understanding of migratory strategies and the reasons for their high variability along the phylogenetic tree remains relatively poor. Most of the hypotheses relating to migration have been formulated for terrestrial taxa; classically, oceanic migrations were considered as merely dispersive because of the scarcity of observations in the open ocean. We describe for the first time, the migration strategy of a small seabird, the Bulwer's petrel (Bulweria bulwerii), and provide new insights into the ecology and evolution of long-distance marine migrations. LOCATION: Subtropical and tropical Atlantic Ocean. METHODS: Using cutting-edge geolocators, we examined the year-round distribution and at-sea activity patterns of adult Bulwer's petrels sampled at five localities throughout the species' breeding range in the Atlantic, within the Azores, Salvages, Canary and Cape Verde archipelagos. We assessed the migratory connectivity of the species and its habitat use at population and metapopulation scales. RESULTS: Our results provide the first evidence of an oriented leapfrog migration in oceanic seabirds. Ecological niche models based on breeding-season data effectively predicted that subtropical waters of the South Atlantic would be the preferred habitat for the northern populations of Bulwer's petrels during the non-breeding season. Habitat modelling also highlighted similarities in distributions between the breeding and non-breeding periods for the southern populations. Data on at-sea activity patterns suggested that birds from the northern and southern populations behave differently during the breeding season, as well as in the northern and southern non-breeding ranges during the non-breeding period. MAIN CONCLUSIONS: These results indicate that specific habitat preferences, presumably related to differences in prey availability, explain the observed distributions and hence the pattern of leapfrog migration described for Bulwer's petrel. Our study demonstrates the utility of integrating diverse tracking data from multiple populations across international boundaries, and habitat modelling, for identifying important areas common to many marine species in the vast oceanic environments.